Preparation method of Fe-doped SnS2 and SnO2 heterojunction catalyst loaded on foamed nickel

By preparing Fe-doped SnS2 and SnO2 heterojunction catalysts on nickel foam, the problem of irreversible reconstruction of transition metal sulfides at high potential is solved, the stability of the catalyst and the efficiency of nitrogen reduction reaction are improved, and more efficient Nitrogen reduction synthesis process.

CN119287426APending Publication Date: 2025-01-10QINGDAO UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411385879.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

Transition metal sulfides are irreversiblely reconstituted at high potentials, shortening the service life of the catalyst, reducing catalytic activity and stability, and limiting the efficiency and performance of electrocatalytic nitrogen reduction synthesis of ammonia.

Method used

The nanosheet-like structure is prepared by hydrothermal technology by using Fe-doped SnS2 and SnO2 heterojunction catalysts supported on nickel foam, and Fe-doped treatment is carried out at high potential to improve the electron mobility and cyclic stability of the catalyst.

Benefits of technology

It significantly improves the activity and stability of the catalyst, enhances the efficiency of nitrogen reduction reaction and the circulation performance of the material, and extends the service life of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119287426A_ABST
    Figure CN119287426A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a Fe-doped SnS2 and SnO2 heterojunction catalyst loaded on foamed nickel, and relates to an electrocatalytic material technology. The preparation method of the Fe-doped SnS2 and SnO2 heterojunction catalyst loaded on the foamed nickel comprises the following steps: S101, selecting SnCl4. 5H2O as a tin source, and preparing a SnO2 (at) NF precursor on a foamed nickel substrate; s102, drying the obtained precursor, and vulcanizing by adopting a hydrothermal technology to obtain a nanosheet-shaped SnS2 and SnO2 heterojunction, and S103, immersing the dried heterojunction into a ferric nitrate solution, and calcining after immersing to obtain the Fe-doped SnS2 and SnO2 heterojunction catalyst. The invention relates to a multi-element heterogeneous metal material prepared by a specific method and application thereof, the multi-element heterogeneous nano material prepared by the method has the advantages of simple process flow, accurate control of the morphology of the material, easy execution of the operation process, uniform size of the prepared material, and high specific surface area.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of electrocatalytic materials, and in particular to a method for preparing a Fe-doped SnS2 or SnO2 heterojunction catalyst supported on nickel foam. Background Art

[0002] Ammonia is an important chemical raw material in the fields of fertilizers, coatings, etc., and is the second most produced commercial chemical. At present, more than 90% of ammonia is prepared by the Haber-Bosch process, which requires high temperature and high pressure conditions, high energy consumption and dependence on the use of fossil fuels, producing a large amount of CO2 emissions. In the new era of advocating energy conservation and environmental protection, this process faces serious energy consumption and environmental protection problems. The electrocatalytic nitrogen reduction ammonia synthesis process is an energy-saving process driven by electric energy, and the raw materials are green and environmentally friendly H2O and N2, which is expected to replace the traditional ammonia synthesis process. However, there are some technical difficulties in this process that need to be overcome, which makes its ammonia production rate, Faraday efficiency and other performances not high, and there is a large gap from commercial production.

[0003] In recent years, non-precious metal electrocatalytic materials have attracted widespread attention. Given that the performance of single-component catalysts is still unsatisfactory, combining two or more catalytic materials to construct heterogeneous structures has become an effective strategy to improve catalyst activity. It can not only produce electron redistribution at the interface and achieve synergistic effects by combining different components, but also produce new interface structures by changing the composition and crystal phase of the structure to achieve efficient full water splitting catalytic function. Chemical doping can change the composition and structure of electrocatalysts at the molecular level, improving the thermodynamics and kinetics of electrocatalytic reactions.

[0004] Studies have shown that SnO2 nanoparticles prepared by hydrothermal synthesis have found ideal small nanoparticles with relatively more lattice defects, which have good electrocatalytic performance. At the same time, transition metal sulfur compounds SnS2 have adjustable electronic structures and controllable morphologies, showing excellent activity in electrocatalysis. However, the irreversible reconstruction of transition metal sulfur compounds at high potentials will shorten the service life of the catalyst and reduce the catalytic activity and stability. Summary of the invention

[0005] 1. Technical issues to be resolved

[0006] In view of the shortcomings of the prior art, the present invention provides a method for preparing Fe-doped SnS2 and SnO2 heterojunction catalysts supported on nickel foam, which solves the problem that the irreversible reconstruction of transition metal sulfur compounds at high potential will shorten the service life of the catalyst and reduce the catalytic activity and stability.

[0007] (II) Technical solution

[0008] To achieve the above objectives, the present invention is implemented through the following technical solutions:

[0009] A method for preparing a Fe-doped SnS2 or SnO2 heterojunction catalyst supported on nickel foam, comprising the following steps:

[0010] S101 selected SnCl4·5H2O as the tin source and prepared SnO2@NF precursor on nickel foam substrate using hydrothermal technology;

[0011] S102: drying the obtained precursor, and then performing sulfurization by hydrothermal technology to obtain nanosheet SnS2 and SnO2 heterojunction;

[0012] S103: immersing the dried heterojunction in an iron nitrate solution, and then calcining the solution to obtain Fe-doped SnS2 and SnO2 heterojunction catalysts;

[0013] Through the above technical solution, Fe doping can effectively improve the catalytic performance of SnS2 and SnO2 heterojunctions, increase electron mobility, and improve the efficiency of catalytic reactions.

[0014] Furthermore, the SnO2@NF precursor is prepared according to the following steps:

[0015] NaOH was added to deionized water, and an equal volume of anhydrous ethanol was added dropwise during stirring. SnCl4·5H2O was added to the above solution, and a white precipitate was generated after stirring for 10 minutes. The supernatant and the precipitate were separated after standing for 30 minutes, and the nickel foam was immersed in the supernatant. The spherical SnO2@NF structure composed of nanoparticles was accurately prepared by hydrothermal technology at 200℃ for 2 hours.

[0016] Through the above technical solution, uniform growth of nanoparticles can be achieved during the hydrothermal reaction, thereby improving the catalytic performance of the material.

[0017] Further, the equivalent ratio of SnCl4·5H2O to NaOH is 1:7;

[0018] Through the above technical solution, the excess NaOH helps to ensure the complete precipitation of SnO2, forming a uniform white precipitate and improving the purity of the product.

[0019] Furthermore, the vulcanization process is prepared by the following steps:

[0020] Weigh a certain amount of thioacetamide and dissolve it in deionized water, then add 10% acetic acid solution by volume to the above solution, stir for 5 minutes, immerse the SnO2@NF precursor in the above mixed solution, and react at 150°C for 3 hours by hydrothermal technology to obtain flaky SnS2 and SnO2 heterojunction catalysts;

[0021] Through the above technical scheme, the presence of SnS2 can improve the activity of the catalyst, making it show a higher reaction rate in the photocatalytic reaction.

[0022] Furthermore, the volume ratio of the thioacetamide to the acetic acid solution is 1:1;

[0023] Through the above technical scheme, the ratio can effectively adjust the reaction conditions, promote the complete dissolution and reaction of thioacetamide, and ensure the uniformity of the product.

[0024] Furthermore, the Fe-doped SnS2, SnO2 heterojunction composite is prepared according to the following steps:

[0025] The SnS2 and SnO2 heterojunction catalysts were immersed in a ferric nitrate solution, and the pH was adjusted to 1.5 after immersion treatment for 6 hours. After drying, the solution was calcined at 350°C for 3 hours to obtain Fe-doped SnS2 and SnO2 heterojunction catalysts.

[0026] Through the above technical solution, iron doping can improve the electron transport performance, increase the activity of the catalyst, and facilitate the photocatalytic reaction.

[0027] Furthermore, the concentration of the ferric nitrate solution is 0.05 mol·L -1 ;

[0028] Through the above technical solution, the concentration can effectively control the iron doping amount and avoid crystal defects and decreased catalytic performance caused by excessive doping.

[0029] Furthermore, the calcination heating rate was 5 °C min -1 ;

[0030] Through the above technical solution, a slower heating rate helps to ensure uniform temperature inside the material and improve consistency during the calcination process.

[0031] Furthermore, Fe-doped SnS2 and SnO2 heterojunction catalyst materials are prepared by the preparation method of the present application.

[0032] (III) Beneficial effects

[0033] The present invention provides a method for preparing a Fe-doped SnS2 or SnO2 heterojunction catalyst supported on nickel foam, which has the following beneficial effects:

[0034] 1. The present invention provides a method for preparing a Fe-doped SnS2 and SnO2 heterojunction catalyst loaded on nickel foam, which combines metal doping technology with heterostructure engineering and plays a more critical role in the field of electrocatalytic nitrogen reduction. In the heterostructure, the presence of the interfacial electric field can effectively improve the conductivity of the material. SnS2 and SnO2 are combined in the form of a heterojunction. Since they contain hydrated O-2p and S-3p orbitals, oxysulfides are more resistant to self-oxidation than metal sulfides. In addition, when trace amounts of Fe are doped into the main material, the electronic properties of Sn-3d change, generating more electrochemical reaction edge active sites. At the same time, the addition of iron to the heterostructure will cause the area where the charge is concentrated to form a stronger local electric field, which is conducive to the adsorption of nitrogen reduction intermediates, and plays an important role in improving the electrochemical performance of the composite material. More importantly, the chemical bonding can effectively promote charge transfer on the interface, thereby improving the rate performance and cycle stability of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 It is a flow chart of the Fe-doped SnS2 and SnO2 heterojunction catalyst supported on nickel foam provided by an embodiment of the present invention.

[0036] Figure 2 This is a scanning electron microscope (SEM) image of the Fe-doped SnS2 and SnO2 heterojunction catalyst loaded on nickel foam prepared in the embodiment provided in the embodiment of the present invention, and the sample is a wrinkled nanosheet.

[0037] Figure 3 It is the SEM spectrum of the intermediate products at different stages of the preparation provided in the embodiments of the present invention, and the sample morphology can be accurately synthesized.

[0038] Figure 4 The scanning electron microscope mapping (SEM mapping) map provided by the embodiment of the present invention shows the uniform distribution of the two elements.

[0039] Figure 5 This is a high-resolution transmission electron microscope (TEM) spectrum provided by an embodiment of the present invention, and the sample has an obvious heterogeneous interface.

[0040] Figure 6 It is a comparison chart of the catalytic performance of Fe-doped SnS2 and SnO2 heterojunction catalysts supported on nickel foam prepared in the examples provided in the embodiments of the present invention. DETAILED DESCRIPTION

[0041] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0042] Embodiment 1:

[0043] like Figure 1 As shown, the present invention provides a method for preparing a Fe-doped SnS2, SnO2 heterojunction catalyst supported on nickel foam, comprising the following steps:

[0044] S101 selected SnCl4·5H2O as the tin source and prepared SnO2@NF precursor on nickel foam substrate using hydrothermal technology;

[0045] S102: drying the obtained precursor, and then performing sulfurization by hydrothermal technology to obtain nanosheet SnS2 and SnO2 heterojunction;

[0046] S103: immersing the dried heterojunction in an iron nitrate solution, and then calcining the solution to obtain Fe-doped SnS2 and SnO2 heterojunction catalysts;

[0047] Fe doping can effectively improve the catalytic performance of SnS2 and SnO2 heterojunctions, increase electron mobility, and improve catalytic reaction efficiency.

[0048] The SnO2@NF precursor was prepared according to the following steps: NaOH was added to deionized water, an equal volume of anhydrous ethanol was dropped during stirring, SnCl4·5H2O was added to the above solution, a white precipitate was generated after stirring for 10 minutes, the supernatant and the precipitate were separated after standing for 30 minutes, and the foamed nickel was immersed in the supernatant. The spherical SnO2@NF structure composed of nanoparticles was accurately prepared by hydrothermal technology at 200°C for 2 hours. During the hydrothermal reaction, the uniform growth of nanoparticles can be achieved, and the catalytic performance of the material is improved. The equivalent ratio of SnCl4·5H2O to NaOH is 1:7. The excess NaOH helps to ensure the complete precipitation of SnO2, forming a uniform white precipitate and improving the purity of the product.

[0049] The sulfurization process is prepared by the following steps: weigh a certain amount of thioacetamide and dissolve it in deionized water, then add a 10% volume fraction acetic acid solution to the above solution, stir for 5 minutes, immerse the SnO2@NF precursor in the above mixed solution, and react at 150°C for 3 hours through hydrothermal technology to obtain flaky SnS2 and SnO2 heterojunction catalysts. The presence of SnS2 can improve the activity of the catalyst, making it show a higher reaction rate in the photocatalytic reaction. The volume ratio of thioacetamide to acetic acid solution is 1:1. This ratio can effectively adjust the reaction conditions, promote the complete dissolution and reaction of thioacetamide, and ensure the uniformity of the product.

[0050] The Fe-doped SnS2 and SnO2 heterojunction composite is prepared according to the following steps: the SnS2 and SnO2 heterojunction catalyst is immersed in an iron nitrate solution, the pH is adjusted to 1.5 after immersion treatment for 6 hours, and then the mixture is dried and calcined at 350°C for 3 hours to obtain the Fe-doped SnS2 and SnO2 heterojunction catalyst. The iron doping can improve the electron transport performance, increase the activity of the catalyst, and contribute to the photocatalytic reaction. The concentration of the iron nitrate solution is 0.05 mol·L -1 This concentration can effectively control the amount of iron doping, avoiding crystal defects and catalytic performance degradation caused by excessive doping. The calcination heating rate is 5℃·min -1 , a slower heating rate helps ensure uniform temperature within the material and improves consistency during calcination.

[0051] Fe-doped SnS is prepared by the preparation method of the present application. 2、 SnO2 heterojunction catalyst material.

[0052] Embodiment 2:

[0053] Preparation of Fe-doped SnS2, SnO2 heterojunction catalyst supported on nickel foam according to the present invention

[0054] First, weigh 576.0 mg NaOH and dissolve it in 40 mL deionized water. Add 40 mL anhydrous ethanol dropwise under stirring. Add 841.4 mg SnCl4·5H2O under stirring. Stir for 5 minutes to generate a white turbid liquid. Let it stand for 30 minutes. Transfer the supernatant to a stainless steel autoclave, immerse 2 cm*2 cm nickel foam, heat to 200 ° C, and keep it warm for 24 hours. After cooling to room temperature, wash it with deionized water and anhydrous ethanol several times, and dry it at 60 ° C overnight to obtain a white solid.

[0055] Weigh 901 mg of thioacetamide, dissolve it in 20 mL of deionized water, and dissolve it by ultrasonic. Measure 2 mL of glacial acetic acid, dissolve it in 20 mL of deionized water, and drop the thioacetamide solution into it while stirring. After stirring evenly, transfer it to a stainless steel autoclave, put in SnO2@NF, heat it to 150°C, and keep it warm for 3 hours. After cooling to room temperature, wash it with deionized water and anhydrous ethanol several times, and dry it at 100°C for 3 hours to obtain a yellow solid.

[0056] Weigh 2 g of ferric nitrate nonahydrate, dissolve it in 20 mL of deionized water, immerse it in the SnS2 and SnO2 heterojunction catalyst and stir it at room temperature for 6 hours. After adjusting the pH to 1.5, take out the material, dry it at 80°C for 24 hours, and then heat it to 500°C and calcine it for 3 hours to obtain a black solid catalyst.

[0057] The properties of the final product were observed, such as Figure 2 , Figure 3 , Figure 4 and Figure 5 shown.

[0058] Figure 2 This is a scanning electron microscope (SEM) image of the Fe-doped SnS2 and SnO2 heterojunction catalyst supported on nickel foam prepared in Example 1 provided in the embodiments of the present invention. The sample is in the shape of a wrinkled nanosheet.

[0059] Figure 3 It is a scanning electron microscope (SEM) spectrum of different intermediates prepared in Example 1 provided in the examples of the present invention.

[0060] Figure 4 The scanning electron microscope mapping (SEM mapping) map provided in Example 1 of the present invention shows the uniform distribution of each element.

[0061] Figure 5 The high-resolution transmission electron microscopy (HRTEM) spectrum provided in Example 1 of the present invention shows that there is an obvious heterogeneous interface in the material, corresponding to the two heterogeneous phases of SnS2 and SnO2.

[0062] Embodiment 3:

[0063] The Fe-doped SnS2 and SnO2 heterojunction catalyst supported on nickel foam provided in an embodiment of the present invention comprises the following steps:

[0064] First, weigh 0.5g NaOH and dissolve it in 40mL deionized water. Then, add 40mL anhydrous ethanol dropwise under stirring. Then, add 0.85g SnCl4·5H2O under stirring. After stirring for 5min, a white turbid liquid is generated. After standing for 30min, the supernatant is transferred to a stainless steel autoclave, immersed in 1cm*2cm nickel foam, and heat at 200℃ for 24h. After cooling to room temperature, wash and dry at 60℃ to obtain a white solid.

[0065] Weigh 0.9g of thioacetamide, dissolve it in 20mL of deionized water, and dissolve it by ultrasonic. Measure 10% acetic acid solution, drop it into the thioacetamide solution, stir it evenly, transfer it to a stainless steel autoclave, put in the white solid material, heat it at 150℃, and keep it warm for 3h. After cooling to room temperature, wash it with deionized water and anhydrous ethanol, and dry it at 100℃ to obtain a yellow solid.

[0066] Weigh 2 g of ferric nitrate nonahydrate, dissolve it in 20 mL of deionized water, immerse it in the SnS2 and SnO2 heterojunction catalyst and stir it at room temperature for 6 hours. After adjusting the pH to 1.5, take out the material, dry it at 80°C for 24 hours, and then heat it to 500°C and calcine it for 3 hours to obtain a black solid catalyst.

[0067] Embodiment 4:

[0068] The NRR electrocatalytic performance test experiment was carried out in a two-chamber H-type electrolyzer separated by a Nafion211 membrane, with 0.1M KOH solution as the electrolyte. At room temperature, an electrochemical workstation (CHI760E) with a standard three-electrode system was used to perform electrochemical tests of all samples in 0.1M KOH. The working electrode was made of prepared iron-doped SnS2 and SnO2 heterojunction catalysts. Calibration was performed with reference to the reference and converted to a reversible oxygen electrode (RHE) by the formula.

[0069] E (RHE) =E (Hg / HgO) +0.89

[0070] Before measuring NRR, the electrolyte was bubbled with ultra-high purity N2 (99.999%) for 30 min. To explore the NRR activity, linear sweep voltammetry was performed from 0 V to 1.8 V at a scan rate of 5 mV / s.

[0071] According to the above method, the performance of the iron-doped heterojunction catalysts and their intermediates prepared in Examples 2-3 was tested respectively. Figure 6 shown.

[0072] The LSV polarization curve can not only calculate the overpotential, but also compare the LSV curves under N2 and Ar atmospheres. The difference in the LSV curves under the two atmospheres can be used to determine the potential range and NRR activity of the nitrogen reduction reaction. The ammonia production was tested using indophenol blue and Nessler's reagent methods and the corresponding Faraday efficiency was calculated. It can be clearly seen from the figure that the iron-doped heterojunction catalyst prepared according to the present invention has excellent nitrogen reduction performance and long-term stability.

[0073] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a Fe-doped SnS2, SnO2 heterojunction catalyst supported on nickel foam, characterized in that: The following steps are involved: S101 selected SnCl4·5H2O as the tin source and prepared SnO2@NF precursor on nickel foam substrate using hydrothermal technology; S102: drying the obtained precursor, and then performing sulfurization by hydrothermal technology to obtain nanosheet SnS2 and SnO2 heterojunction; S103: immersing the dried heterojunction into a ferric nitrate solution, and then calcining the solution to obtain Fe-doped SnS2 and SnO2 heterojunction catalysts.

2. The method for preparing a Fe-doped SnS2, SnO2 heterojunction catalyst supported on nickel foam according to claim 1, characterized in that: The SnO2@NF precursor is prepared according to the following steps: NaOH was added to deionized water, and an equal volume of anhydrous ethanol was dropped into the solution during stirring. SnCl4·5H2O was added to the above solution and stirred for 10 minutes to generate a white precipitate. The supernatant and the precipitate were separated after standing for 30 minutes, and the nickel foam was immersed in the supernatant. The spherical SnO2@NF structure composed of nanoparticles was accurately prepared by hydrothermal technology at 200°C for 2 hours.

3. The method for preparing a Fe-doped SnS2, SnO2 heterojunction catalyst supported on nickel foam according to claim 1, characterized in that: The equivalent ratio of SnCl4·5H2O to NaOH is 1:

7.

4. The method for preparing a Fe-doped SnS2, SnO2 heterojunction catalyst supported on nickel foam according to claim 1, characterized in that: The vulcanization process is prepared by the following steps: Weigh a certain amount of thioacetamide and dissolve it in deionized water. Then add 10% acetic acid solution by volume to the above solution and stir for 5 minutes. Immerse the SnO2@NF precursor in the above mixed solution and react at 150°C for 3 hours through hydrothermal technology to obtain flaky SnS2 and SnO2 heterojunction catalysts.

5. The method for preparing a Fe-doped SnS2, SnO2 heterojunction catalyst supported on nickel foam according to claim 1, characterized in that: The volume ratio of the thioacetamide to the acetic acid solution is 1:

1.

6. The method for preparing a Fe-doped SnS2, SnO2 heterojunction catalyst supported on nickel foam according to claim 1, characterized in that: The Fe-doped SnS2, SnO2 heterojunction composite is prepared according to the following steps: The SnS2 and SnO2 heterojunction catalysts were immersed in ferric nitrate solution, and the pH was adjusted to 1.5 after immersion treatment for 6 hours. After drying, they were calcined at 350° C. for 3 hours to obtain Fe-doped SnS2 and SnO2 heterojunction catalysts.

7. The method for preparing a Fe-doped SnS2, SnO2 heterojunction catalyst supported on nickel foam according to claim 1, characterized in that: The concentration of the ferric nitrate solution is 0.05 mol·L -1 .

8. The method for preparing a Fe-doped SnS2, SnO2 heterojunction catalyst supported on nickel foam according to claim 1, characterized in that: The calcination heating rate was 5℃·min -1 .

9. The Fe-doped SnS2 and SnO2 heterojunction catalyst materials are prepared according to the preparation method described in any one of claims 1 to 8.